The Effect Of Use Of Roler Size And CVT Spring Variations On Engine Performance - Yuniarto Agus Winoko; Aji Irwanda (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The rollers regulate the pulley diameter based on engine speed, and acceleration can be increased by sliding rollers. This research tested torque and fuel consumption (SFC) between sliding rollers and CVT spring variations. The sliding rollers were tested at 10g, 13g and 16g, while the CVT springs were tested at 800 rpm, 1000 rpm and 1500 rpm. The test method uses full throttle opening, with data analyzed using Excel, ANOVA and Minitab. The independent variables are the sliding roller and CVT spring variations, while the fixed variable is 92 Octane fuel. The results of the research are 10g Roller: Highest torque 8.16 Nm at 6000 rpm, lowest 4.09 Nm at 9000 rpm, highest fuel consumption 0, 1256 kg/HP/hour at 9000 rpm, lowest 0.0807 kg/HP/hour at 6500 rpm. Roller 13g: Highest torque 8.77 Nm at 6500 rpm, lowest 4.52 Nm at 9000 rpm, highest fuel consumption 0.1249 kg/HP/hour at 9000 rpm, lowest 0.0804 kg/HP/hour at 5500 rpm . Roller 16g: Highest torque 8.55 Nm at 7500 rpm, lowest 5.40 Nm at 5000 rpm, highest fuel consumption 0.1225 kg/HP/hour at 9000 rpm, lowest 0.0807 kg/HP/hour at 6500 rpm .